PENGARUH PENDIDIKAN, KOMPETENSI, KOMPENSASI, MOTIVASI, DAN KOMITMEN ORGANISASI PADA KINERJA BENDAHARA SEKOLAH MENENGAH DI KABUPATEN GIANYAR - Kasmini, Ni Wayan Ayu; Wirama, Dewa Gede; Wirakusuma, Made Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
This study is aimed to determine the effect of education, competence, compensation, motivation, and organizational commitment on the performance of BOS treasurers. The study was conducted on the BOS treasurers of the entire Junior High Schools in Gianyar Regency using primary data through questionnaire which has met the validity and reliability testing. Survey respondents were 43 BOS treasurers obtained by using saturated sample or census. The data was analyzed using multiple linear regressions, preceed by the classic assumption test. The results of this study show that education has no effect on the performance of the BOS treasurers, while competencies, compensations, motivations, and organizational commitment have positive effects on the performance of the BOS treasurers. Competence most dominantly affects the performance of the BOS treasurers.
Keywords: education, competencies, compensation, motivation, commitment